PERBANDINGAN PRODUKSI CABAI MERAH (Capsicum annum, L.) ANTARA YANG MENGGUNAKAN MEDIA TANAM SEKAM BAKAR KOMPOS DENGAN SEKAM BAKAR PUPUK KANDANG SEBAGAI SUMBER BELAJAR BIOLOGI SMA - Anggraini, Dewi; Widowati, Hening (Bioedukasi Jurnal Pendidikan Biologi, 2013)
This research was carried out in Yosomulyo village Metro Pusat Districk, Metro City. Objective of this reasearch was: (1) To know the different of red chili (Capsicum annum, L.) production beetwen using burn husk compost media plant and burn husk manure media plant. (2) To  know the highest red chili (Capsicum annum, L) production beetwen using burn husk compost media plant and burn husk manure media plant. The methode for this research wed experiment methode. With two treatments, for each treatment have 16 samples red chili plant. The data take with weighing the crop, and analyzing wed normalitas and homogenitas, so was gotten the result of the research as wellfor two level equation test got thit 23,68 > tdaf 2,04 at obvious level α = 0,05, with the result thit > tdaf, refuse H0 and the meaning  that any obvious difference of red chili production between use burn husk compost media plant and use burn husk manure media plant. For the two level difference test got thit 23,68 > 1,70 at obvious level α = 0,05 with the result thit > tdaf, refuse H0 and the meaning to the average red chili production with the burn husk compost media plant higher than production with the burn husk manure media plant. For education world, this research used the source for study biology subject about growth and development material.   Kata kunci:  media sekam bakar kompos, sekam bakar pupuk kandang, produksi cabai.